Integrated development of regional airports - Stepanenko A.S.; Kurenkova E.O. (Научно-технический вестник Брянского государственного университета)
The article discusses the state of the air transport industry in order to study the regional air transport system and identify new costeffective solutions for its development, based on the influence of various external factors — political, economic, social. An analysis of the project of the air transport holding «Novaport» was made; the key performance indicators of the creation of the holding system are analyzed, as well as the main advantages of the aviation holding in the conditions of the «turbulent» market environment. The system of state subsidizing of the regional air transport system was studied — the financial indicators of the state program: «Development of the transport system» are presented.A systematic analysis of the results of the activities of the regional air holding showed that during the period of turbulence in the external environment, subsidies do not provide sufficient assistance for the development of air transport enterprises, so the project of creating regional air transport holdings should be considered as a way of integrated and cost-effective development of regional air transportation. Also, the cooperation of the enterprises of the industry will create conditions for maintaining stability in the market, each of the members of the holding, which in modern conditions is extremely important for regional air transport systems.